Initial oxidation kinetics of Si(113)-(3 × 2) investigated using supersonic seeded molecular beams - Ohno, S.; Tanaka, K.; Kodama, H.; Tanaka, M.; Yoshigoe, A.; Teraoka, Y. (Surface Science, 2020)
[Display omitted] The initial oxidation of silicon surfaces with (113) orientation has been investigated using high-resolution photoelectron spectroscopy with synchrotron radiation. In the present study, we investigated both the Si 2p state and the O 1s state to evaluate the oxide thickness and composition, and to assess the strain at the SiO2/Si interface. The oxidized components in the Si 2p state (Si1+, Si2+, Si3+, Si4+) were analyzed. In the O 1s state, a low-binding-energy component (LBC) and a high-binding-energy component (HBC) were analyzed. To investigate the non-thermal oxidation process, we utilized supersonic seeded molecular beam (SSMB) to obtain oxygen molecules with high translational kinetic energies (Et). We demonstrate that the oxide quality and oxidation kinetics are largely altered by changing the value of Et.